Manager Support Predicts Turnover of Professionals in India - TYMON, Walter G. (Institutional Knowledge at Singapore Management University, 2011)
The purpose of this paper is to examine how the support managers provide to employees affects the employees' sense of intrinsic reward, personal commitment, perceived career success, and retention. A large-scale employee survey wss conducted of 28 organizational entities in India involving 9,301 randomly identified employees yielding 4,811 respondents (54 percent response rate) supported by employee interviews following the survey. Using a hypothesis-driven, path analytic-regression approach, the managerial support of employees had significant direct and indirect effects on perceived career success and retention one year later. Intrinsic rewards and personal commitment mediated these relationships. Managers may play a much greater role in employee retention than the literature often suggests. Key manager practices include showing personal interest, holding career discussions, acknowledging employee contributions, using a system of empowerment, and celebrating milestones and successes. Employees can improve their perceived career success by balancing their long- and short-term goals, improving their competence, and communicating openly with their managers. To reduce turnover, HR professionals can provide better manager support training, hold managers accountable for retention, enhance the career management and HR systems by developing more non-monetary rewards, and learn from those that leave. Manager practices in support of their employees were studied across a large and diverse set of national, international, and global firms operating in India. Findings highlight the importance of the managerial role in reducing turnover and enhancing perceptions of career success in a culture known for high power distance among managers and employees.